The concept of Wasatiyyah under Islamic law perspective: a manifestation of just and balanced rule - Hj Ibrahim, Badruddin; Mohd, Azizah; Hussin, Nasimah; Zawawi, Majdah; Mohd Kamal, Mohd Hisham; Jusoh, Hamid; Arifin, Mahamad; Mohd Napiah, Mohammad Deen; Omar, Muhammad Naim; Ab Aziz, Shamrahayu (2021)
This article seeks to examine the concept of wasatiyyah that is employed and incorporated in various Islamic legal principles and rules of fiqh. Even though such wasatiyyah concept is embodied in various subjects of Islamic law (fiqh), nevertheless, this chapter will only demonstrate several subjects that incorporate wasatiyyah as one of its criteria serving as examples. Therefore, not limited to these preferred subjects, this chapter will discuss the concept of wasatiyyah that is characterized and reflected in several concepts under Islamic jurisprudence (Usul al-Fiqh), Islamic Family Law, Islamic Criminal law, Islamic law on International Relations, Islamic law of Finance as well as Islamic procedural laws Civil and Criminal.